32 Web-based Camera (NICView) as a sense of proximity tool: a Quality-Improvement initiative for parents of neonates admitted in the NICU. (19th August 2020) - Kalaniti, Kaarthigeyan; Mugarab-Samedi, Veronica; Riehl, Adel; Bingham, William; Daspal, Sibasis
Abstract: Background: Family-centered care (FCC) is an important approach and a vital component in healthcare. However, implementation of FCC model in a clinical setting presents a challenge. Effective parent-health care provider relationships are very essential in NICU especially when treatment is complex during the management of critically-ill neonates. Web-based camera (WBC) systems have been used in a few NICUs in the USA and the UK, allowing virtual visitation of the family members. However, to the best of our knowledge, there is no center in Canada that has utilized this WBC (NICView ®) service. NICView® is a WBC mounted to the baby's bed, which is streaming 'live' video around-the-clock to parents and families. We report the perception of parents and their satisfaction after using NICView® facility in our NICU. Objectives: Our goal was to see if the WBC system reduced the anxiety and stress level in parents by exploring NICView ® as a tool to enhance FCC model. This study was designed to explore the perception of parents and their satisfaction levels during their newborns stay within our NICU. Design/Methods: A prospective, questionnaire-based study conducted over 6-month period. Determinants that may facilitate or disrupt the use of a commercially-available camera device were identified. After signing an informed consent form, the parents utilized the camera service continuously throughout the newborn stay within the NICU, except during the times of procedures, feedings and routine baby care. Demographic information of parents was collected in the questionnaire, along with along satisfaction questions. Parents filled out the questionnaires after 1-week of utilization of the camera or sooner if the baby was getting discharged. Results: 94 respondents completed the questionnaire. Parental perception was consistent with earlier studies. Almost all parents used the service on a regular basis, twenty NICView cameras had more than 7000 logins by respondents during study period. Family members residing out of Saskatoon or out-of-SK and in some instances out-of-Canada used it the most, especially working fathers or distant grandparents. Seventy-five percent of the respondents were mothers. Almost 89% of parents reported having the WBC system helped reduce their anxiety and stress levels. All parents (100%) recommended this WBC system to other parents and strongly agreed that NICView was easy to use. Nearly 98% of parents agreed that they felt very connected with their baby using the WBC system. Frequently reported comments were on the positioning of camera like incorrect camera placement that did not offer a good view of the baby, the need to call nurses sometimes to turn on or adjust the camera after care, using the chat option to adjust the camera position when moved away. After we saw these frequent comments, we had to reiterate to bed-side nurses to re-position the camera if moved away and reminded parents to make use of the NICView® 24-hr customer support service available offered by the company. Conclusion: Almost all parents perceived WBC very beneficial in the NICU. Our study supported the concept that the NICView® service was very useful for parents when it was not possible for them to visit the NICU. In a tertiary hospital where parents are geographically distant, the WBC service is a good alternative to promote bonding and a good Q.I tool.